Extra- and intranuclear heat perception and triggering mechanisms in plants - Yang, Xiaolong; Guan, Hongling; Yang, Yinghua; Zhang, Yiting; Su, Wei; Song, Shiwei; Liu, Houcheng; Chen, Riyuan; Hao, Yanwei (Frontiers in Plant Science, 2023)
The escalating impact of global warming on crop yield and quality poses a significant threat to future food supplies. Breeding heat-resistant crop varieties holds promise, but necessitates a deeper understanding of the molecular mechanisms underlying plant heat tolerance. Recent studies have shed light on the initial events of heat perception in plants. In this review, we provide a comprehensive summary of the recent progress made in unraveling the mechanisms of heat perception and response in plants. Calcium ion (Ca2+), hydrogen peroxide (H2O2), and nitric oxide (NO) have emerged as key participants in heat perception. Furthermore, we discuss the potential roles of the NAC transcription factor NTL3, thermo-tolerance 3.1 (TT3.1), and Target of temperature 3 (TOT3) as thermosensors associated with the plasma membrane. Additionally, we explore the involvement of cytoplasmic HISTONE DEACETYLASE 9 (HDA9), mRNA encoding the phytochrome-interacting factor 7 (PIF7), and chloroplasts in mediating heat perception. This review also highlights the role of intranuclear transcriptional condensates formed by phytochrome B (phyB), EARLY FLOWERING 3 (ELF3), and guanylate-binding protein (GBP)-like GTPase 3 (GBPL3) in heat perception. Finally, we raise the unresolved questions in the field of heat perception that require further investigation in the future.